Efficacy and safety of single-branched stent graft in the treatment of type B aortic dissection: a meta-analysis of cohort studies - Wenxiao Lin; Fuyuan Cai; Jinliang Yan; Xiaolei Lin (Journal of Cardiothoracic Surgery)
Abstract Background Thoracic aortic endovascular repair (TEVAR) is the most commonly employed method for treating type B aortic dissection (TBAD). One of the primary challenges in TEVAR is the reconstruction of the left subclavian artery (LSA). Various revascularization strategies have been utilized, including branch stent techniques, fenestration techniques, chimney techniques, and hybrid techniques. Among these, the single-branched stent graft (SBSG) has emerged as one of the most promising methods. This study employs a meta-analysis to evaluate the efficacy and safety of SBSG in treating TBAD, thereby providing robust evidence to guide clinical practice. Methods Published literatures on the treatment of TBAD with SBSG were collected from CNKI, Wanfang Data, VIP, PubMed, Embase, Web of Science and Cochrane Library. The search period ranged from the inception of each database to December 1, 2024. The quality of the included studies was assessed using the Newcastle-Ottawa Scale. Meta-analysis was conducted using RevMan 5.3 software. Results A total of eight studies involving 660 participants were included in this meta-analysis. The results demonstrated that, compared to other surgical methods, SBSG significantly reduced the perioperative neurological complication rate (OR = 0.23, 95%CI(0.07, 0.76), P = 0.02), type I endoleak rate (OR = 0.30, 95%CI(0.15, 0.61), P = 0.001), and left upper limb ischemia rate (OR = 0.06, 95%CI(0.01, 0.49), P = 0.008). Additionally, SBSG was associated with a shorter operation time (SMD = 0.59, 95%CI(0.04, 1.14), P = 0.04). However, no significant differences were observed between SBSG and other surgical methods in terms of technique success rate (OR = 1.51, 95%CI(0.55, 4.14), P = 0.42), hospital length of stay (OR = 1.51, 95%CI(0.55, 4.14), P = 0.42), aortic false lumen thrombosis rate (OR = 1.30, 95%CI(0.55, 3.07), P = 0.56), pulmonary infection rate (OR = 0.50, 95%CI(0.16, 1.58), P = 0.24), and 30-day postoperative mortality (OR = 0.41, 95%CI(0.12, 1.35), P = 0.41). Conclusion SBSG demonstrates safety and efficacy in the treatment of TBAD by significantly reducing the perioperative neurological complexity rate, type I leakage rate, and left upper limb ischemia rate, while also decreasing operative time.